Effect of Sintering on Hydroxyapatite/Sodium Alginate Properties - Kanasan, Nanthini; Syed Abu Bakar, Sharifah Adzila; Mustaffa, Nor Azimah; Abdol Rahman, Mohd Nasrull; Hassan, Mohd Fahrul; Panerselvan, Gurubaran (International Journal of Integrated Engineering, 2018)
In the present work, a precipitation method was used to prepare a nanocomposite powders consisting of hydroxyapatite and sodium alginate by varying the composition of sodium alginate. The characterization of powder are analyzed by using Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD). SEM is used to identify the morphology and agglomeration of powder while, XRD analysis is used to identify the phase of samples with an increase in the composition of sodium alginate up to 10%. Green samples were prepared and sintered at temperature 1000ËšC and 1100ËšC and the sintered samples are studied based on their phase stability, density and Vickers hardness .The result indicates that there is no secondary phase change happen in this XRD result. The density of HA/SA are increasing relative to hardness for composition ratio 99.5/0.5%. The maximum density were attained by 99.5/0.5% (HA/SA) at 2.12g/cm3 and 2.16g/cm3 for 1000ËšC and 1100ËšC respectively while, the maximum hardness were also attained by 99.5/0.5% for temperature 1000Â°C and 1100Â°C at 0.53GPa and 0.62GPa respectively. FESEM images of pure hydroxyapatite are fully disbursed in sodium alginate and the particles size are in agglomerate conditions.Â